2022
DOI: 10.1101/2022.10.18.512697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct contact guidance mechanisms in single endothelial cells and in monolayers

Abstract: In many tissues, cell shape and orientation are controlled by a combination of internal and external biophysical cues. Anisotropic substrate topography is a ubiquitous cue that leads to cellular elongation and alignment, a process termed contact guidance, whose underlying mechanisms remain incompletely understood. Additionally, whether contact guidance responses are similar in single cells and in cellular monolayers is unknown. Here, we address these questions in vascular endothelial cells (ECs) that in vivo f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…We have recently studied the mechanisms underlying contact guidance in human umbilical vein endothelial cells (HUVECs) cultured on fibronectin-coated polydimethylsiloxane (PDMS) microgrooves (Fig. 1A) (Leclech et al, 2023). In the course of these investigations, we came across the observation that for a microgroove depth of ~5 µm, the cell nuclei exhibited significant out-of-plane deformation and penetration into the grooves, in addition to the planar nuclear elongation and alignment associated with contact guidance (Fig.…”
Section: D Nuclear Deformations In Microgrooves Are Observed In Vario...mentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently studied the mechanisms underlying contact guidance in human umbilical vein endothelial cells (HUVECs) cultured on fibronectin-coated polydimethylsiloxane (PDMS) microgrooves (Fig. 1A) (Leclech et al, 2023). In the course of these investigations, we came across the observation that for a microgroove depth of ~5 µm, the cell nuclei exhibited significant out-of-plane deformation and penetration into the grooves, in addition to the planar nuclear elongation and alignment associated with contact guidance (Fig.…”
Section: D Nuclear Deformations In Microgrooves Are Observed In Vario...mentioning
confidence: 99%
“…In this context, we have been using microgroove substrates as idealized models of the anisotropic subcellular topography of the vascular basement membrane . Our recent studies using these substrates have demonstrated their ability to control vascular endothelial cell morphology, cytoskeletal organization, and collective migration (Leclech et al, 2022(Leclech et al, , 2023.…”
Section: Introductionmentioning
confidence: 99%